Report on Indians taxed and Indians not taxed in the United States (except Alaska) at the eleventh census, 1890 - United States. Census Office. 11th census, 1890. (Washington D.C. : Government Printing Office, 1894)
"The Superintendent of Census may employ special agents or other means to make an enumeration of all Indians living within the jurisdiction of the United States, with such information as to their condition as may be obtainable, classifying them as to Indians taxed and Indians not taxed."
Statement of responsibility from head of title.
Includes index.
Reproduction of the original from the Bruce Peel Special Collections Library, University of Alberta.
Keywords: Indians of North America -- Social conditions -- 19th century; Indians of North America -- Government relations; Indians of North America -- History; United States -- Census, 1890.